 8. MORE RESULTS ON RESTRICTED IDENTITIES

22

Proof.

A ÷

A

and

A u

A

are determined by each other by the following

formulas:

A ÷

A

= (

A u

A

)

÷

A

and

A u

A

= (

A ÷

A

)

÷

Base(

A

)

.

Prove the formulas: (

A u

A

)

÷

A

=

d

n

A

(

X

A

)

X

∈Au

A

o

=

d

n

A

(

X

A

)

X

∈A

o

=

A ÷

A

.

(

A ÷

A

)

÷

Base(

A

) =

d

n

A

(

X

A

)

X

∈A

o

÷

Base(

A

) =

d

Base(

A

)

(

Y

Base(

A

))

Y

d

n

A

(

X

A

)

X

∈A

o

=

(by properties of filter bases) =

d

n

Base(

A

)

(

X

A

Base(

A

))

X

o

=

d

n

Base(

A

)

(

X

A

)

X

∈A

o

=

A u

A

.

That this defines a bijection, follows from

A ÷

A

∼ A u

A

what easily follows

from the above formulas.

Proposition

2153

.

(

ι

X,Y

f,

id

Rel

(Dst

f

)

Y

f

id

Rel

(Src

f

)

X

)

f

Rel

(

A,B

)

is a function and more-

over is an (order and semigroup) isomorphism, for sets

X

Src

f

,

Y

Dst

f

.

Proof.

ι

X,Y

f

= (

X, Y,

GR

f

(

X

×

Y

)); id

Rel

Y

f

id

Rel

X

= (Src

f,

Dst

f,

GR

f

(

X

×

Y

)). The isomorphism (both order and semigroup) is evident.

Proposition

2154

.

(

ι

X,Y

f,

id

FCD

(Dst

f

)

Y

f

id

FCD

(Src

f

)

X

)

f

FCD

(

A,B

)

is a function and more-

over is an (order and semigroup) isomorphism, for sets

X

Src

f

,

Y

Dst

f

.

Proof.

From

symmetry

it

follows

that

it’s

enough

to

prove

that

(

E

Y

f,

id

FCD

Y

f

)

f

FCD

(

A,B

)

is a function and moreover is an (order and semigroup) isomor-

phism, for a set

Y

Dst

f

.

Really,

n

(

hE

Y

i

x,

h

id

FCD

Y

i

x

)

x

Dst

f

o

=

n

(

x

÷

Y,x

u

Y

)

x

Dst

f

o

is an order isomorphism by proved

above.

This implies that

(

E

Y

f,

id

FCD

Y

f

)

f

FCD

(

A,B

)

is an isomorphism (both order and

semigroup).

Proposition

2155

.

(

ι

X,Y

f,

id

RLD

(Dst

f

)

Y

f

id

RLD

(Src

f

)

X

)

f

RLD

(

A,B

)

is a function and more-

over is an (order and semigroup) isomorphism, for sets

X

Src

f

,

Y

Dst

f

.

Proof.

ι

X,Y

f

=

(

X, Y,

(up

f

)

÷

(

X

×

Y

));

id

RLD

Y

f

id

RLD

X

=

(Src

f,

Dst

f,

(up

f

)

u

(

X

×

Y

)). They are order isomorphic by proved above.

ι

Y,Z

g

ι

X,Y

f

=

E

Dst

g,Z

g

◦ E

Y,

Src

g

◦ E

Dst

f,Y

f

◦ E

X,

Src

f

=

E

Dst

g,Z

g

id

RLD

Y

id

RLD

Y

f

◦ E

X,

Src

f

because

E

Y,

Src

g

◦ E

Dst

f,Y

= id

Rel

Y

= id

Rel

Y

id

Rel

Y

. Thus

by proved above

(

(

ι

Y,Z

g

ι

X,Y

f,

id

RLD

Z

g

id

RLD

Y

id

RLD

Y

f

id

RLD

X

)

f

RLD

(

A, B

)

)

is a bijection.

Can three last propositions be generalized into one?